2022
DOI: 10.3389/fonc.2022.729177
|View full text |Cite
|
Sign up to set email alerts
|

Novel and Specific MRI Features Indicate the Clinical Features of Patients With Rare Hepatic Tumor Epithelioid Hemangioendothelioma

Abstract: ObjectiveTo investigate the MRI features and clinical significance of hepatic epithelioid hemangioendothelioma (HEHE).MethodsClinical records and MRI findings were retrospectively evaluated in nine HEHE patients from May 2010 to January 2020.ResultThere were 121 lesions in nine patients with a predominantly peripheral distribution. Five lesions (4.13%) in two patients (22.22%) had evidence of capsular retraction, and three patients had lung metastasis (33.33%). Dynamic contrast-enhanced MRI showed progressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…These were called “slow outs.” Among all patients, no washout was observed in all lesions within the first 60 s; in four patients, the washout started at 60–180 s (36.36%), and in another four (36.36%); it started at 180–300 s. The remaining three patients showed no signs of washout even at 360 s (27.27%) ( Table 3 ). Therefore, on CEUS, all lesions showed an enhancement pattern of “fast in and slow out” (FISO), which was consistent with the pathological features reported in the literature ( 11 ); that is, these imaging features were more suggestive of expansile growth and benign lesions ( 12 , 13 ). These results were significantly different from CECT ( p = 0.008) ( Table 4 ).…”
Section: Resultssupporting
confidence: 87%
“…These were called “slow outs.” Among all patients, no washout was observed in all lesions within the first 60 s; in four patients, the washout started at 60–180 s (36.36%), and in another four (36.36%); it started at 180–300 s. The remaining three patients showed no signs of washout even at 360 s (27.27%) ( Table 3 ). Therefore, on CEUS, all lesions showed an enhancement pattern of “fast in and slow out” (FISO), which was consistent with the pathological features reported in the literature ( 11 ); that is, these imaging features were more suggestive of expansile growth and benign lesions ( 12 , 13 ). These results were significantly different from CECT ( p = 0.008) ( Table 4 ).…”
Section: Resultssupporting
confidence: 87%
“…Usually, the tumor was detected occasionally with no symptom. The characteristic MRI appearances of HEH have been reported, such as coalescent lesion, subcapsular lesion, capsular retraction, lollipop sign and target sign (5,16,17). We have concluded the MRI appearances of 57 HEH patients and the results showed that capsular retraction and lollipop sign were specific features of HEH, which could be used for differential diagnosis (5).…”
Section: Discussionmentioning
confidence: 97%
“…Enhancement can vary and present as mild homogeneous enhancement seen on all phases or thin ring-like enhancement in the arterial phase, with progressive enhancement in the portal venous phase (171) (Figure 9). The characteristic imaging sign is the “lollipop” sign, which is due to tumor spread along the portal and hepatic vein branches and sinusoids, resulting in vascular and sinusoidal narrowing and obstruction (172). As a result, there is tapering of the portal and hepatic vein branches as they approach the lesion.…”
Section: Solid Liver Lesionsmentioning
confidence: 99%